Childhood abuse, body shame, and addictive plastic surgery : the face of trauma - Constantian, Mark B.; Sanchez, Ruston (Ruston J.); Corwin, David L. (New York, NY : Routledge, 2019)
"Childhood Abuse, Body Shame, and Addictive Plastic Surgery explores the psychopathology that plastic surgeons can encounter when seemingly excellent surgical candidates develop body dysmorphic disorder postoperatively. By examining how developmental abuse and neglect influence body image, addictions, and adult health, this highly-readable book uncovers the childhood sources of body dysmorphic disorder. Written from the unique perspective of a leading plastic surgeon with extensive experience in this area and featuring many poignant clinical vignettes and groundbreaking trauma research, this heavily-referenced text offers a new explanation for body dysmorphic disorder that provides help for therapists and surgeons and hope for patients"--
Where the thread began: what surgeons learn from patients and their families -- What the mental health literature says about body dysmorphic disorder -- The valley of the shadow: core issues and parenting -- Body image and body image disorders -- The ways we suffer: body shame and the astounding spectrum of its ravages -- The ways we medicate: addictions and behaviors most relevant to body image -- The effects of trauma on brain and body -- Behavior, PTSD, and surgical compulsion in plastic surgery patients: trailing the trauma prevalence -- Adverse childhood events in medical and plastic surgery patients and their effects on adult health, personality, and surgical happiness -- Resilience: the antidote and the inspiration.
OCLC-licensed vendor bibliographic record.
Keywords: Body dysmorphic disorder; Body image disturbance; Surgery, Plastic; Psychic trauma in children; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / Surgery / Plastic & Cosmetic; MEDICAL / Mental Health; PSYCHOLOGY / Mental Health